THE IMPACT OF BANKING NETWORK SERVICES THROUGH PROFITABILITY ON INDONESIA BANKING COMPANIES - Susy SUHENDRA, Euphrasia; INDRAYANI, Emmy; RAGASARI, Dia; ERNESTIVITA, Gesty (Economy and Sociology, 2021)
The banking sector has embraced the use of technology to serve its clients faster and also to do more with less. Emerging technologies have changed the banking industry from paper and branch based banks to digitized and networked banking services. ATM machines and the number of switching networks is among the technologies used in the banking industry. The aim of this study is to analyze the influence of network switching and number of ATM machine through non-interest income to profitability. The paper proposes to examine whether the number of ATM machines of the bank affect the fee-based income, whether the amount of ATM switching network membership of the bank affects the bank’s fee-based income, and whether the feebased income affects the performance of the bank. The study was conducted in banking companies belonging to members of the switching principal network appointed by Bank Indonesia and switching network companies in Indonesia. The data used for this research is represented by financial statements from Indonesian commercial banks that have gone public, data from banking magazines and data available from each bank’s page avaiolable for open access. The number of samples from this study is represented by 30 commercial banks that are listed in IDX. The results of this study show that the number of ATM machines has no significant effect on Fee Based Income. At the same time, the number of switching networks has a significant effect toward Fee Based Income, and the Fee Based Income has no significant effect on the bank’s return on investment.